2023
DOI: 10.1089/tmr.2023.0011
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Use to Address Cardiovascular Disease and Hypertension in the United States: A Systematic Review and Meta-Analysis, 2011–2021

Abstract: Background: The use of telehealth for the management and treatment of hypertension and cardiovascular disease (CVD) has increased across the United States (U.S.), especially during the COVID-19 pandemic. Telehealth has the potential to reduce barriers to accessing health care and improve clinical outcomes. However, implementation, outcomes, and health equity implications related to these strategies are not well understood. The purpose of this review was to identify how telehealth is being used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our findings show that telehealth is currently being utilized to help manage hypertension in primary healthcare. It also helps to provide remote access to healthcare professionals and enables the monitoring of blood pressure [37,95]. It has been increasingly used during the COVID-19 pandemic to ensure continuity of care and improve access to healthcare services [104].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that telehealth is currently being utilized to help manage hypertension in primary healthcare. It also helps to provide remote access to healthcare professionals and enables the monitoring of blood pressure [37,95]. It has been increasingly used during the COVID-19 pandemic to ensure continuity of care and improve access to healthcare services [104].…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth has shown benefits for hypertension management in primary healthcare. It has the potential to reduce barriers to accessing healthcare and improve clinical outcomes [37]. Telehealth interventions have been used to treat patients with hypertension, heart failure, and stroke, with most interventions employing a team-based care approach [38].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO defines telehealth as “the delivery of health care services, where distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for diagnosis, treatment, and prevention of disease and injuries, research and evaluation, and for the continuing education of health care professionals, all in the interests of advancing the health of individuals and their communities” [ 35 ]. Telehealth is commonly used across the US, particularly amplified during the COVID-19 pandemic [ 36 ]. It has revolutionized healthcare by offering patients consistent access to healthcare professionals without the need for physical travel, which is especially beneficial for those with mobility issues or living in remote areas.…”
Section: Reviewmentioning
confidence: 99%
“…[7] Previous systematic reviews and meta-analyses showed that HBPM is relatively convenient and more accessible and acceptable to patients, and exhibits comparable reproducibility and capability of predicting outcomes, thereby presenting great potential for increasing long-term treatment adherence and stimulating other lifestyle changes. [8][9][10][11][12][13] Clinical trials have indicated the facilitating roles of HBPM, [8][9][10][11][12][13] and key hypertension guidelines also recommend incorporating the use of HBPM as part of clinical practice. [14][15][16][17][18][19] However, despite the promising prospect of HBPM and the increased ownership of HBPM, the effective utilization of HBPM is rather conditional.…”
Section: Introductionmentioning
confidence: 99%